Ocular Manifestations In Hiv Positive Patients Attending Khyber Teaching Hospital Peshawar (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Human immunodefi ciency virus (HIV) infection is a global health problem. Around 90% of infected persons live in developing countries, particularly those in sub-Saharan Africa and Southeast Asia. Ocular manifestations occur in approximately 70% of these patients. The objective of this study was to document ocular manifestations in HIV positive patients attending Khyber Teaching Hospital Peshawar, Pakistan. Methodology: It was a descriptive case series. The study was conducted at Khyber Teaching Hospital Peshawar from January to December 2007. A total of 14 patients were examined. These patients underwent complete ocular examination including assessment of visual acuity, pupillary reaction, ocular motility, ocular adnexa, anterior segment and posterior segment. CD4 count was done in all the patients. Results: Out of the 14 patients examined 6 (42.9%) had ocular manifestations, all of whom were male. The ocular manifestations included herpes simplex keratitis, herpes zoster ophthalmicus with neurotrophic keratitis, iridocyclitis, HIV retinopathy, retinal vasculitis and cytomegalovirus retinitis in one patient each. Amongst those with ocular manifestations, 5 patients (83.3%) had CD4 cell count of 100/mm3 or less and 1 patient (16.7%) had CD4 count between 101 and 200/mm3; and the mode of transmission was homosexual contact in 5 patients (83.3%) and vertical transmission in 1 patient (16.7%). Conclusion: Ocular manifestations occur in a considerable number of HIV positive patients particularly in those with CD4 cell count less than 100/mm3. Therefore, all HIV positive patients should be screened for ocular manifestations. DOI: http://dx.doi.org/10.3126/saarctb.v8i2.5899 SAARCTB 2011; 8(2): 31-36